1998
DOI: 10.1038/sj.leu.2400956
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous T cell lymphomas: mycosis fungoides, Sezary syndrome and HTLV-I-associated adult T cell leukemia (ATL) in Mali, West Africa: a clinical, pathological and immunovirological study of 14 cases and a review of the African ATL cases

Abstract: Cutaneous T cell lymphomas (CTCL) are rare lymphoproliferative diseases, which are frequently suspected to be of viral origin. As very few data were available concerning cutaneous T cell lymphomas in tropical Africa, we undertook a clinical, histopathological, immunological and viro-molecular study of patients with a clinical diagnosis of cutaneous lymphoma, in Bamako, Mali. While prior to this study, no case of CTCL had been reported in this country, 14 patients (five women, nine men; mean age 58 years) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…The presence of HTLV-1 has been reported in various Sahara countries, particularly Morocco, 23 Tunisia, 24 Egypt, 25 Mali, 11 Mauritania, and Algeria, and LTR analyses of some of these isolates have identified the North African subgroup of the cosmopolitan subtype (HTLV-1aD). 6 The phylogenetic analyses of all the cosmopolitan isolates from our patients, together with other previously described isolates from Guinea Bissau and Senegal, 12,26 showed that they belonged to the HTLV-1aD subgroup.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The presence of HTLV-1 has been reported in various Sahara countries, particularly Morocco, 23 Tunisia, 24 Egypt, 25 Mali, 11 Mauritania, and Algeria, and LTR analyses of some of these isolates have identified the North African subgroup of the cosmopolitan subtype (HTLV-1aD). 6 The phylogenetic analyses of all the cosmopolitan isolates from our patients, together with other previously described isolates from Guinea Bissau and Senegal, 12,26 showed that they belonged to the HTLV-1aD subgroup.…”
Section: Discussionmentioning
confidence: 97%
“…7 HTLV-1 is widespread in sub-Saharan Africa, particularly in West and Central Africa. In West Africa, the reported rates of seropositivity for anti-HTLV-1 antibodies vary from 1% to more than 5% among blood donors and/or pregnant women in Ghana, 8 Benin, 9 Burkina Faso, 10 Mali, 11 Senegal, 12 Nigeria, 13 and Guinea Bissau. 14 The prevalence of HTLV-1 infection in Guinea Bissau is one of the highest in Africa.…”
mentioning
confidence: 95%
“…A few years later, it was described in Caribbean immigrants living in United Kingdom (Catovsky et al, 1982) and afterwards reported in other endemic areas, including the Caribbean region (Gibbs et al, 1987;Hanchard, 1996), Africa (Fouchard et al, 1998) and South America (Matutes et al, 1994;Gerard et al, 1995). Following the initial description of ATL ) the epidemiologic clustering of ATL within certain age groups in localized areas of southern Japan instigated the interest by Japanese investigators that the malignancy could be virally induced.…”
Section: Adult T-cell Leukemiamentioning
confidence: 99%
“…Moreover, most of the epidemiological studies have been performed in hospitalized patients or in individuals at risk for acquiring HTLV-1 (prostitutes, human immunodeficiency virus [HIV]-infected patients, etc.) or in rural populations (2,10,15,34,35). Therefore, very few data have been reported thus far for large populations of blood donors from west or central Africa (1,9,12).…”
mentioning
confidence: 99%